The Role of Civil Servants' Digital Literacy in Public Services Through The Mediation of The Adoption of Sorong Smart City Technology - Andrester Bleskadit; Tri Lestari Hadiati; Karmanis Karmanis (International Forum of Researchers and Lecturers, 2026)
This study aims to analyse the role of digital literacy of the State Civil Apparatus (ASN) in supporting the implementation of smart cities and improving the quality of public services in the Sorong City Regional Secretariat. The research method used is qualitative with a descriptive approach, through in-depth interviews with structural officials within the Sorong City Secretariat. The results of the study show that the level of digital literacy of civil servants is still varied and greatly influenced by the duties and functions of the position, generational background, and the intensity of the use of digital technology in daily work. The implementation of the smart city concept in Sorong City has not been fully optimal due to limited infrastructure, readiness of human resources, budget support, and coordination between regional apparatus organisations. Nevertheless, digitalisation has had a positive impact on the efficiency of public services, especially in the aspects of administration, transparency, and ease of access to information for the public. This study also found that the success of digital governance is highly determined by the commitment of regional leaders, internal policies that support the digital capacity building of civil servants, and continuous training and mentoring. Therefore, strengthening the digital literacy of civil servants is a strategic and sustainable priority policy to support the development of smart cities and digital public services that are effective, inclusive, and accountable in Sorong City.